2015
DOI: 10.1007/s10681-015-1552-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids

Abstract: Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This is not a surprising result owing to allosyndesis between the chromosomes of maize and Z. perennis in MTP (Iqbal et al 2019). Such chromosomal translocation between the maize chromosomes and those of Z. perennis has occurred in the previous maize × Z. perennis hybrids (Cheng et al 2016, Iqbal et al 2018.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This is not a surprising result owing to allosyndesis between the chromosomes of maize and Z. perennis in MTP (Iqbal et al 2019). Such chromosomal translocation between the maize chromosomes and those of Z. perennis has occurred in the previous maize × Z. perennis hybrids (Cheng et al 2016, Iqbal et al 2018.…”
Section: Resultsmentioning
confidence: 81%
“…For example, McGISH was successfully used to confirm the hybrid status and chromosome translocation in the maize-Z. perennis hybrids (Cheng et al 2016, Iqbal et al 2018 and the maize-T. dactyloides-Z. perennis hybrids (Iqbal et al 2019, Li et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The cross between colchicine-treated tetraploid maize (2n = 4x = 40)and Z. perennis (2n = 4x = 40) could give rise to allotetraploid F1 (2n = 4x = 40) that showed normal meiosis and higher pollen viability (Shaver 1964). Previous studies have confirmed that five chromosomes from "A" genome of maize shared higher homology with 10 chromosomes from Z. perennis (Schnable et al 2011;Cheng et al 2016).…”
Section: Introductionmentioning
confidence: 68%
“…The genetic bridges (usage of a third parent in between two parents) can break crossing barriers in between divergent species (Hussain and Williams 1997;Reagon and Snow 2006) and choice of small DNA fragments (translocations) can be advantageous to get rid of unwanted traits. Polyploid provides an effective bridge for a controlled induction of alien genes into cultivated crops and the choice of an allopolyploid bridge plant is preferable due to its genome plasticity (Stebbins 1971;Cheng et al 2016), gene redundancy, asexual reproduction (Comai 2005) and allopolyploid's capability to seldom disrupt selfincompatibility barriers (Miller and Venable 2000). Polyploidy and distinct hybridization have already enriched the genetic background of important agricultural crops (Hajjar and Hodgkin 2007), for example wheat (Jiang et al 2017), rice (Shakiba and Eizenga 2014;Ramos et al 2016), maize (Maazou et al 2017), Brassica (Li et al 2014) and tobacco (Hancock and Lewis 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation